Pengaruh Dukungan Orang Tua Dan Kepercayaan Diri Terhadap Prestasi Belajar Siswa Kelas VIII Smp Negeri 6 Pematang Siantar Tahun Ajaran 2022/2023 - Maruli Arta Sidabutar; Sotarduga Sihombing; Paulina Herlina N Sirait (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to gain knowledge about the effect of parental support and self-confidence on the learning achievement of grade VIII students of SMP Negeri 6 Pematang Siantar. This type of research is qualitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The total population in this study was 171 people, and the sample used was 120 people. The sampling technique used is simple random sampling. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and coefficient of determination (R2).The results stated that: 1) There is a positive and significant influence of parental support on student learning achievement is seen in the t test where the calculated value of parental support (2.225) > ttabell (1.6580). 2) There is a positive influence of self-confidence on student learning achievement, this result is seen in the t test where and the calculated value of student learning achievement (3.309) > ttable (1.6580) which means that the variable has an effect. 3) Parental support and self-confidence together affect student achievement, this result can be seen in the F test where the Fcalculate value (18.444) > the Ftable value (2.6821). The R square coefficient of determination test is known to be 0.240, which means that 24% of the variables of parental support and self-confidence affect student achievement at SMP Negeri 6 Pematang Siantar. While 76% is the influence of other variables that were not studied in this study.